CONSTRUCTIONS OF NORMS AND VALUES OF ASEAN TOWARD OF NARCHOTICS SMUGGLING IN SOUTHEAST ASIA - Rendi Prayuda (UIR Press, 2018)
This articles describes the Norms and Values of ASEAN toward of Narchotics Smuggling in Southeast Asia. Southeast Asia are one of part region in the world that was have land area of 4,4 million square kilometers. Based on population data by United Nations Department of Economic and Social Affairs, the populations of ASEAN has increased from 563.7 million in 2006 to 631.8 million in 2015 at a rate of 1,14% per annum. With the bigs of potency from Southeast Asia region that on August 8, 1967 was established The Association of Southeast Asian Nations that have ten member of states are Brunei Darussalam, Malaysia, Lao, Myanmar, Philipine, Singapore, Thailand, Vietnam, Cambodia and Indonesia. Narchotics are one of most threat for human security in Southeast Asia that have drug trends and pattern of always moved and give bad effect for human security in Southeast Asia. This articles use of qualitative methods with descriptive as a technic of the research. The theories applied in this paper are contructivism approach with international security concept, human securities, and narchotics smuggling. This paper have some purposes are to explain the route of narchotics smuggling in Southeast Asia and process of Constructions of Norms and Values of among member states of ASEAN toward of Narchotics Smuggling in Southeast Asia and find some factors that have influence of contructions norm and value that was used of member states that are ASEAN Ways.